Engineering Design Of The Mercur Gold Project Ore Processing Facility (Mining Engineering) - T. W. Turk; S. A. Sass (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1985)
The engineering design features of the Mercur Gold Project crushing, grinding, carbon-in-leach, bullion, reagent, and tailings disposal areas will be discussed in this paper. It presents a project overview and flowsheet along with selected design alternatives. During the engineering phase, major equipment and other features were selected to optimize design within site location and environmental constraints. The project team organization and procedures were adopted to accommodate multiple optimization studies while maintaining a tight engineering schedule.